Linking Smallholders to Markets: Determinants and Impacts of Farmer Collective Action in Kenya - Elisabeth Fischer; Matin Qaim (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
This article investigates determinants and impacts of cooperative organization, using the example of smallholder banana farmers in Kenya. Farmer groups are inclusive of the poor, although wealthier households are more likely to join. Employing propensity score matching, we find positive income effects for active group members. Yet price advantages of collective marketing are small, and high-value market potentials have not yet been tapped. Beyond prices, farmer groups function as important catalysts for innovation adoption through promoting efficient information flows. Some wider implications are discussed under what conditions collective action is useful, and through what mechanisms the potential benefits emerge.
Keywords: 330; agricultural markets; smallholder farmers; collective action; cooperative organization; Kenya; East-Africa